Finanţarea sistemelor de sănătate în ţările Uniunii Europene. România în context european - Doboș, Cristina (Calitatea Vieții, 2008)
This article represents a theoretical analysis regarding different financing mechanisms of the European health systems. The purpose of the article is to draw conclusions upon the advantages and disadvantages of these mechanisms. The question whether a supplemenaryt insurance would be a valid choice for Romania and it would reduce the informal copayments is drawn. The EU supplementary insurance market (which would cover the copayments) is not very developed, with the except of France. In spite of this, a large amount of population is beneficiary of these insurances in covering ambulatory costs, in countries as Austria, Belgium, France, Irland, Spain, etc.